2007
DOI: 10.1002/jcu.20350
|View full text |Cite
|
Sign up to set email alerts
|

A transcranial doppler study in interictal migraine and tension‐type headache

Abstract: Our findings support the arteriolar vasodilatation theory in migraine without aura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 27 publications
(30 reference statements)
4
23
0
Order By: Relevance
“…It is known that ischemic cerebral infarction preferentially affects the posterior cerebral artery distribution in migraine patients (5). However, the vast majority of known studies have evaluated cerebral endothelial function just in the anterior cerebral circulation (9)(10)(11)(12)(13)(14)(15). Hyperreactivity, hyporeactivity, and no difference in reactivity were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that ischemic cerebral infarction preferentially affects the posterior cerebral artery distribution in migraine patients (5). However, the vast majority of known studies have evaluated cerebral endothelial function just in the anterior cerebral circulation (9)(10)(11)(12)(13)(14)(15). Hyperreactivity, hyporeactivity, and no difference in reactivity were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies that evaluated the reactivity of cerebral arteries in migraine patients were performed by measuring changes in the partial arterial pressure of carbon dioxide (CO 2 ) (9)(10)(11)(12)(13)(14)(15). But only a few have specifically compared endothelial function in both cerebral circulations in migraine patients compared to healthy subjects (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Migraine and episodic tension-type headaches may also relate to vascular changes of CBF (5, 6, 8, 10). Nowak et al (19) found that children with migraines and chronic-type headaches had increased CBFV during visual stimulation, due to increased cerebrovasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…Studying neural adaptation through refractory effects may also be of interest in certain disease states of the brain including epilepsy (8), headache disorders (9), and vascular dementia (10). To be useful in investigating these diseases, fMRI must provide insight into individual patient data (i.e., at the single-subject level).…”
mentioning
confidence: 99%